PREVALENCE AND ECOLOGY OF THE BROWN DOG TICK RHIPICEPHALUS SANGUINEUS IN DOMESTIC MAMMALS IN BASRAH PROVINCE, IRAQ, WITH THE ACARICIDAL EFFECT OF QUERCUS BRANTTI ACORNS EXTRACT IN ADULTS. - Hatem, Alaa N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to detect the infestation of Rhipicephalus sanguineus of some mammals in Basrah province from January to June 2019. A total 75 of 210 (35.71%) of studied mammals were been infested. This species was isolated from horses in Iraq for the first time. The highest prevalence was recorded in dogs while the lowest in buffaloes. Mean of intensity was recorded mostly in sheep, and the lowest in horses. Highest relative density was recorded in dogs, whereas the lowest was in horses. The highest occurrence was recorded in April, whereas the lowest was in January. The acaricidal effect of ethanolic extract of acorns Quercus brantti in adults was shown the rates of mortality increases with the rise of extract concentrations. Mortality percentages were increased according to the time of the exposure. Females were more sensitive than males in the treatment with extract.